The critical speed of a moving time-harmonic load acting on a system consisting a pre-stressed orthotropic covering layer and a pre-stressed half-plane - Ilhan, Nihat (ELSEVIER SCIENCE INC, 2012)
The dynamic response of a system consisting of an initially stressed covering layer and an initially stressed half-plane to a moving time-harmonic load is investigated within the scope of the piecewise-homogeneous body model utilizing three-dimensional linearized wave propagation theory in the initially stressed body. It is assumed that the material of the layer and half-plane is orthotropic. It is also assumed that the velocity of the line-located time harmonic moving load which acts on the covering layer is constant. The investigations were carried out were for the plane-strain state under subsonic velocity of the moving load for two types of contact conditions, namely: complete and incomplete. An algorithm is developed for the determination of the values of the moving load's critical velocity. For various values of the problem parameters the numerical results were presented and discussed. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Time-harmonic moving load; Critical velocity; Initial stress; Dynamical response; INTERFACE STRESS-FIELD; SPACE; DYNAMICS; Engineering; Mathematics; Mechanics